2019
DOI: 10.1103/physreva.99.053601
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature properties of interacting bosons on a two-leg flux ladder

Abstract: Quasi-one-dimensional lattice systems such as flux ladders with artificial gauge fields host rich quantum-phase diagrams that have attracted great interest. However, so far, most of the work on these systems has concentrated on zero-temperature phases while the corresponding finitetemperature regime remains largely unexplored. The question if and up to which temperature characteristic features of the zero-temperature phases persist is relevant in experimental realizations. We investigate a two-leg ladder latti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Several interesting properties have been highlighted by a number of works, for both bosonic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and fermionic [53][54][55][56][57][58][59][60][61] flux ladders. Importantly, it was shown that flux ladders, in the quasi-1D limit, can host states that share fundamental properties with 2D FQH states [62][63][64][65], and that can be directly tested in current cold-atom experiments as well as DMRG or MPS simulations [64,65].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Several interesting properties have been highlighted by a number of works, for both bosonic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and fermionic [53][54][55][56][57][58][59][60][61] flux ladders. Importantly, it was shown that flux ladders, in the quasi-1D limit, can host states that share fundamental properties with 2D FQH states [62][63][64][65], and that can be directly tested in current cold-atom experiments as well as DMRG or MPS simulations [64,65].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…exploring the exact parameter regimes that could be accessed in future experiments (including the influence of nearest-neighbor rung-wise interactions, which are typically present in synthetic dimension implementations), investigating the role of finite energy densities and temperatures [40,48,72,77,78] on the ground-state phase diagrams [41], and developing optimal state-preparation and detection protocols (based, for instance, on the dynamics induced by quantum quenches in the flux-ladder model) remain important open questions.…”
Section: Introductionmentioning
confidence: 99%
“…Finite-temperature simulations using DMRG or tensor network techniques beyond ground-state physics were developed early on, but seemed practical mostly for one dimensional systems. The purification method [68,69] is particularly attractive for its simplicity [70][71][72], but in the limit of low temperatures, its representation of the mixed state carries twice the entanglement entropy of the ground state, making it unsuitable for wide ladders, although techniques have been developed to reduce the entanglement growth [73]. The METTS method [66,67] was developed to overcome this obstacle.…”
Section: Introductionmentioning
confidence: 99%